Quedas e auto-eficácia em evitar quedas em idosos comunitários de Fortaleza, Santa Cruz, Belo Horizonte e Barueri: dados do rede fibra - Luana Almeida de Sá Cavaleiro (2019)
Falls in the elderly constitute a complex, multifactorial geriatric syndrome with a profound socio-economic impact in public health. For instance, fear of falling, defined here as being concerned with future falls, is not only a common psychological consequence brought about by previous falls but also a worry found in older population with no history of falling. The consequences resulting from falling and fear of falling encompass clinical, psychological, social and epidemiological domains. Therefore, the study of those consequences requires distinct analytical approaches. Having said that, research on the factors associated with falls are key to planning preventive strategies that secure the elderly’s health, well-being and quality of life. Accordingly, the objective of this study was to analyze factors that contribute to falling as well as falls self-efficacy in community-dwelling older population, residing in the cities of Fortaleza (Ceará), Santa Cruz (Rio Grande do Norte), Belo Horizonte (Minas Gerais) and Barueri (São Paulo), from data collected though the Rede FIBRA (Rede de Estudos de Fragilidade em Idosos Brasileiros) program. A secondary objective was to compare the elderly with regard to socio-demographic, economic, physical and functional health conditions considering housing and to explore the association of these variables. The first study analyzed factors that contributed to falling and falls self-efficacy in 1,854 community-dwelling elders. The dependent variables for this study were number of falls and self-efficacy to avoid falls through Falls Efficacy Scale-International (FES-I Brazil). The independent variables were: sociodemographic aspects (gender, age, schooling, marital status, race, current occupation), health status (number of comorbidities according to self-reported medical diagnosis of chronic diseases in the last year), self- daily life and application of the Katz-Brazil scales for basic activities of daily living and Lawton for instrumental activities of daily living); depressive symptoms by the Geriatric Depression Scale and subjective health assessment. The data was analyzed using binomial logistic regression, i.e. stepwise regression, of predictor variables for falls and self-efficacy. The results showed that low education levels, greater comorbidity and medication use, and diminished activities of daily living, both basic and advanced, all relate to falls in the elderly at a 70.9% rate. Moreover, the number of comorbidities together with diminished instrumental activities of daily living predict self-efficacy in preventing falls at a 63.6% rate. The second study compared the number of falls and the level of falls self-efficacy as reported by community-dwelling elders, this time combined in two distinct sub-groups representing Northeastern Brazil (n=866) and Southeastern Brazil (n=988). The application of the self-efficacy scale in avoiding falls of took into consideration the subjects’ sociodemographic characteristics as well as their physical functional abilities. It was compared: number of falls; self-efficacy in preventing falls through FES-I Brazil; demographic partner aspects; number of comorbidities; drug index; body mass index (BMI); palmar grip strength (FPP) by (Jamar dynamometer), walking speed a distance of 4.6 meters; advanced activities of daily living (AAVD); basic activities of daily living (ABVD); instrumental activities of daily living (AIVD) and subjective health assessment. Comparisons using Pearson's Chi-square test or Fisher's exact test and Student's t-test. Significance of 5%. The comparative analysis showed that the number of comorbidities, number of medications, body mass index, muscle strength, gait velocity, instrumental activities of daily living, advanced daily life activities and health perception (p <0.05). The mean scores on the self-efficacy scale in avoiding falls and the proportion of elderly with low scores were significantly higher in the Northeast region (p <0.05).For the Southeastern sub-group, the analysis showed a significant correlation to the number of comorbidities, the amount of medication, body mass index, muscular strength, gait speed, instrumental activities of daily living, advanced activities of daily living and overall health perception (p< 0.05). Other analyzes did not present significant statistical difference (p> 0.05). The average of the scale score as well as the incidence of low scores were significantly higher in the Northeastern sub-group (p< 0.05). In these ways, he results of this study show that the following factors influence falls: low education levels; greater number of comorbidities and amount of medication; and diminished basic and advanced activities of daily living. The results of the study also show that greater number of comorbidities together with instrumental activities of daily living co-relate to falls self-efficacy. Additionally, the two sub-groups differed in their falls self-efficacy scale as well as in their sociodemographic characteristics and physical functional abilities, pointing to better conditions in southeast cities.